2017
DOI: 10.1074/jbc.m116.764720
|View full text |Cite
|
Sign up to set email alerts
|

Correctors and Potentiators Rescue Function of the Truncated W1282X-Cystic Fibrosis Transmembrane Regulator (CFTR) Translation Product

Abstract: Edited by Thomas Sö llnerW1282X is the fifth most common cystic fibrosis transmembrane regulator (CFTR) mutation that causes cystic fibrosis. Here, we investigated the utility of a small molecule corrector/ potentiator strategy, as used for ⌬F508-CFTR, to produce functional rescue of the truncated translation product of the W1282X mutation, CFTR 1281 , without the need for readthrough. In transfected cell systems, certain potentiators and correctors, including VX-809 and VX-770, increased CFTR 1281 activity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
113
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(126 citation statements)
references
References 52 publications
13
113
0
Order By: Relevance
“…However, the expression of this shorter CFTR can be increased by incubation with VX-809 ( Fig. 1C), as reported previously (Haggie et al 2017). Although the full-length read-through protein was not detected, even with G418 treatment (Fig.…”
Section: Chloride Currents Carried By a Mixture Of C-terminus Truncatsupporting
confidence: 88%
See 2 more Smart Citations
“…However, the expression of this shorter CFTR can be increased by incubation with VX-809 ( Fig. 1C), as reported previously (Haggie et al 2017). Although the full-length read-through protein was not detected, even with G418 treatment (Fig.…”
Section: Chloride Currents Carried By a Mixture Of C-terminus Truncatsupporting
confidence: 88%
“…; Haggie et al . ; Mutyam et al . ; ClinicalTrials.gov Identifier: NCT03624101 (https://clinicaltrials.gov/ct2/show/NCT03624101)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a panel of known CFTR modulators was tested, including correctors VX-809, VX-661, C3, and C18, which target the NBD1-MSD interface, 9 C4, which targets NBD2, 16 CoPo-22, a CFTR modulator with dual corrector and potentiator function, 12 and W1282X corr -A23, which corrects CFTR 1281 , the protein product generated by the W1282X-CFTR nonsense mutation. 17 None of these correctors increased ΔF508-NBD1 cell surface expression; nor did previously described potentiators VX-770 and PG-01.…”
Section: Resultsmentioning
confidence: 92%
“…A recent study showed that VX-770 acts additively with VX-809 to restore CFTR function in chronically treated R117H/ ΔF508 cells [52]. Surprisingly however, increased chloride conductance was not seen in W1282X cells despite the presence of adequate transcript levels when treated with both VX-770 and VX-809 [53]. As the combination of VX-770 and VX-809 (i.e., Orkambi) is now used clinically for treating patients carrying the ΔF508 mutation, it seems fitting to rigorously examine its effects on other CF mutations to potentially extend its application.…”
Section: Ongoing Challenges and Future Perspectivesmentioning
confidence: 99%